Changes of the potential distribution area of French Mediterranean forests under global warming - Gaucherel, C.; Guiot, J.; Misson, L. (Biogeosciences, 2008)
This work aims at understanding future spatial and temporal distributions of tree species in the Mediterranean region of France under various climates. We focused on two different species (Pinus Halepensis and Quercus Ilex) and compared their growth under the IPCC-B2 climate scenario in order to quantify signiﬁcant changes between present and future. The inﬂuence of environmental factors such as atmospheric CO2 increase and topography on the tree growth has also been quantiﬁed. We modeled species growth with the help of a processbased model (MAIDEN), previously calibrated over measured ecophysiological and dendrochronological series with a Bayesian scheme. The model was fed with the ARPEGE – MeteoFrance climate model, combined with an explicit increase in CO2 atmospheric concentration. The main output of the model gives the carbon allocation in boles and thus tree production. Our results show that the MAIDEN model is correctly able to simulate pine and oak production in space and time, after detailed calibration and validation stages. Yet, these simulations, mainly based on climate, are indicative and not predictive. The comparison of simulated growth at end of 20th and 21st centuries, show a shift of the pine production optimum from about 650 to 950 m due to 2.5 K temperature increase, while no optimum has been found for oak. With the direct effect of CO2 increase taken into account, both species show a signiﬁcant increase in productivity (+26 and +43% for pine and oak respectively) at the end of the 21st century. While both species have different growth mechanisms, they have a good chance to extend their spatial distribution and their elevation in the Alps during the 21st century under the IPCC-B2 climate scenario. This extension is mainly due to the CO2 fertilization effect.
Keywords: climate modeling (voyant); CO2; Pinus halepensis; Quercus ilex; tree growth

Holocene climatic change in Morocco: a quantitative reconstruction from pollen data - Cheddadi, R.; Lamb, H. F.; Guiot, J.; van der Kaars, S. (Climate Dynamics, 1998)
Annual precipitation, July and January tem- peratures were reconstructed from a continuous Holo- cene pollen sequence from the Middle Atlas, Morocco, using the best modern analogues method. The recon- structions show a clear difference between the early and late Holocene: from &10 ka to &6.5 ka the climate was drier and warmer than during the period since 6.5 ka. The average value of annual precipitation was &870mm until 6.5 ka, then rose to &940 mm. Be- tween 10 ka and 6.5 ka January and July temperatures were about 4 °C higher than the present. Both temper- atures show a marked decrease between 7 ka and 6 ka. After 6.5 ka July and January temperatures fluctuated between 21 and 23 °C, and 2.5 and 5 °C respectively. January temperatures show a period of intermediate values (&3.5 °C) between 4 ka and 5.5 ka. The recon- structed climate values generally match palaeolim- nological data from the same core, which show five intervals of low lake level during the Holocene. They are also consistent with regional-scale COHMAP simulated palaeoclimate that shows contrasting pat- terns of rainfall variation between the northwester- nmost part of Africa and the intertropical band
APSAPS
Keywords: climate; Holocene; Morocco; paleoclimate; pollen